Real‐world treatment patterns and outcomes using terlipressin in 203 patients with the hepatorenal syndrome. Issue 2 (4th June 2020) - Moore, Kevin; Jamil, Khurram; Verleger, Katharina; Luo, Linlin; Kebede, Nehemiah; Heisen, Marieke; Corman, Shelby; Leonardi, Roberta; Bakker, Rachel; Maï, Christine; Shamseddine, Nisreen; Huang, Xingyue; et al.
Summary: Background: Hepatorenal syndrome and acute kidney injury are common complications of decompensated cirrhosis, and terlipressin is recommended as first‐line vasoconstrictor therapy. However, data on its use outside of clinical trials are lacking. Aims: To assess practice patterns and outcomes around vasoconstrictor use for hepatorenal syndrome in UK hospitals. Methods: This was a multicentre chart review study. Data were extracted from medical records of patients diagnosed with hepatorenal syndrome and treated by vasoconstrictor drugs between January 2013 and December 2017 at 26 hospitals in the United Kingdom. The primary outcome was improvement of kidney function, defined as complete response (serum creatinine improved to ≤1.5 mg/dL), partial response (serum creatinine reduction of ≥20% but >1.5 mg/dL) and overall response (complete or partial response). Other outcomes included need for dialysis, mortality, liver transplantation and adverse events. Results: Of the 225 patients included in the analysis, 203 (90%) were treated with terlipressin (median duration, 6 days; range: 2‐24 days). Mean (±standard deviation) serum creatinine at vasopressor initiation was 3.25 ± 1.64 mg/dL. Terlipressin overall response rate was 73%. Overall response was higher in patients with mild acute kidney injury (baseline serum creatinine <2.25 mg/dL), compared to those with moderate (serum creatinine ≥2.25 mg/dL and <3.5 mg/dL) or severe (serum creatinine ≥3.5 mg/dL). Ninety‐day survival was 86% for all patients (93% for overall responders vs 66% for treatment nonresponders, P < 0.0001). Conclusion: Terlipressin is the most commonly prescribed vasoconstrictor for patients with hepatorenal syndrome in the United Kingdom. Treatment with terlipressin in patients with less severe acute kidney injury (serum creatinine <2.25 mg/dL) was associated with higher treatment responses, and 90‐day survival.